2007
DOI: 10.1093/eurheartj/ehm588
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive detection and quantification of acute myocardial infarction in rabbits using mono-[123I]iodohypericin  SPECT

Abstract: The study indicates the suitability of [(123)I]MIH for in vivo visualization of myocardial infarcts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
79
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 22 publications
1
79
0
Order By: Relevance
“…In nuclear imaging, high signal to background ratios are mandatory for accurate visualization and quantification of I-Hyp/Hyp mixture has shown excellent properties as a cardiac diagnostics due to its unique and selective necrosis avidity (Fonge et al, 2008;Cona et al, 2013b). However, its marked lipophilicity and consequent poor solubility in water is a common limitation in parenteral tracer formulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In nuclear imaging, high signal to background ratios are mandatory for accurate visualization and quantification of I-Hyp/Hyp mixture has shown excellent properties as a cardiac diagnostics due to its unique and selective necrosis avidity (Fonge et al, 2008;Cona et al, 2013b). However, its marked lipophilicity and consequent poor solubility in water is a common limitation in parenteral tracer formulation.…”
Section: Discussionmentioning
confidence: 99%
“…This animal model of infarction was chosen because it has been routinely used to prove the potential application of 123 I-Hyp as diagnostic cardiac agent showing reproducible and accurate results (Fonge et al, 2008;Feng et al, 2013;Cona et al, 2013a). As carrier of 123 I-Hyp/ Hyp, NaCh solutions at different concentrations were prepared for evaluating their solubilizing properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The infarct area was defined as any area with a perfusion value of 60% or less (19)(20)(21). Correlations were calculated, between defect sizes for the TTC and polar maps.…”
Section: Myocardial Perfusion Polar Mapmentioning
confidence: 99%
“…4 However, the long plasma half-life and high blood pool activity make it impossible for early in vivo visualization of necrotic myocardium. 5,6 To seek for superior necrosis avid agents in imaging, we further evaluated the necrosis targetability of monomeric anthraquinones. The results showed that monomeric anthraquinones exhibited necrosis targetability and shorter plasma half-life times.…”
mentioning
confidence: 99%